Energy spectrum of the organic quasi-1D conductors with NNN and correlated hopping - Skorenkyy, Yu.; Kramar, O. (Condensed Matter Physics, 2006)
A model for organic quasi-one-dimensional conductors (TMTTF)₂X and (TMTSF)₂X is considered. The anisotropic
character of these compounds is modelled by two different hopping parameters: t between nearest
neighbors (NN) in a chain of tetramethyl-tetrathiafulvalene (TMTTF) or tetramethyl-tetraselenfulvalene
(TMTSF) molecules and t' between the chains (NNN - between next nearest neighbors). Taking into account
the correlated hopping of electrons allows us to describe the effect of site occupancy on hopping processes.
In a regime of strong intraatomic correlation, high energy processes are cut off by applying two successive
canonical transformations. An effective model is obtained for concentration of electrons n < 1 which contains
kinetic exchange terms of antiferromagnetic (AF) nature. Oppositely, NNN hopping and correlated hopping
disfavor the AF order. The energy spectrum of the effective model is calculated. Application of the obtained
results to quasi-one-dimensional conductors is discussed.